ANALISIS HUBUNGAN TINGKAT PENGETAHUAN, SIKAP DAN PRAKTIK PENGENDALIAN PENYAKIT HOG CHOLERA PETERNAK BABI DI KECAMATAN KOTA RAJA – KOTA KUPANG - Toha, Larry Richard Wellem; Susetya, Heru; Nugroho, Widagdo S. (JURNAL KAJIAN VETERINER, 2022)
For the people of East Nusa Tenggara, pigs do not only have economic value but also have social and cultural values. For this reason, it is necessary to perform a good farming management to keep the pigs free from diseases such as Hog cholera (HC). The aim of this study is to measure the association between pig farmers knowledge and attitude and practice regarding HC controlling in Kota Raja Sub-district, Kupang City. In this study, data was obtained by questionnaire and interview of pig farmers which was done in Kota Raja Sub-district from August until October 2018. Data was analyzed with chi square (χ2) analyses to measure the association between variables. The result of this study show that the knowledge variable is associated with attitude variable with P<0,05 (OR:6,3), but is not significantly associated with practice variable. The attitude variable is associated with practice variable with P<0,01 (OR:0,1). In conclusion, pig farmers in Kota Raja Sub-district need to improve practice regarding HC controlling by improvingnowledge about HC disease, which will improve farmers attitude toward HC controlling programs.